C-banding, fluorescent staining and NOR location in holokinetic chromosomes of bugs of the Neotropical genus Antiteuchus (Heteroptera: Pentatomidae: Discocephalinae) - Lanzone, Cecilia (2006)
Different cytogenetic techniques including C-banding, base-specific fluorochromes and silver nitrate staining were used to compare the karyotypes of three species of bugs, representatives of the Neotropical genus Antiteuchus, namely A. mixtus, A. sepulcralis and A. macraspis. The species have holokinetic chromosomes which is typical of the Hemiptera, and their diploid chromosome number is 2n = 14 and they have an XX/XY (female/male) sex chromosome system. C-banding revealed telomeric blocks of constitutive heterochromatin in most chromosomes of these three species. In each species, CMA;-positive blocks were observed in the telomeric heterochromatin region of chromosome pair 1. This chromosome pair carried the nucleolar organizer region (NOR), which silver nitrate staining revealed is located in the telomeric heterochromatin. In contrast to the result obtained with CMA3, entire chromosome complement stained homogenously with DAPI, except for the telomeric region of pair 1, which remained unstained.